Na+, K+-ATPase subunit composition in a human chondrocyte cell line; evidence for the presence of α1, α3, β1, β2 and β3 isoforms - Mobasheri, Ali; Trujillo, Elisa; Arteaga, Mari-Francis; Martin-Vasallo, Pablo (MDPI, 2012)
Membrane transport systems participate in fundamental activities such as cell cycle control, proliferation, survival, volume regulation, pH maintenance and regulation of extracellular matrix synthesis. Multiple isoforms of Na+, K+-ATPase are expressed in primary chondrocytes. Some of these isoforms have previously been reported to be expressed exclusively in electrically excitable cells (i.e., cardiomyocytes and neurons). Studying the distribution of Na+, K+-ATPase isoforms in chondrocytes makes it possible to document the diversity of isozyme pairing and to clarify issues concerning Na+, K+-ATPase isoform abundance and the physiological relevance of their expression. In this study, we investigated the expression of Na+, K+-ATPase in a human chondrocyte cell line (C-20/A4) using a combination of immunological and biochemical techniques. A panel of well-characterized antibodies revealed abundant expression of the α1, β1 and β2 isoforms. Western blot analysis of plasma membranes confirmed the above findings. Na+, K+-ATPase consists of multiple isozyme variants that endow chondrocytes with additional homeostatic control capabilities. In terms of Na+, K+-ATPase expression, the C-20/A4 cell line is phenotypically similar to primary and in situ chondrocytes. However, unlike freshly isolated chondrocytes, C-20/A4 cells are an easily accessible and convenient in vitro model for the study of Na+, K+-ATPase expression and regulation in chondrocytes.